FAKTOR YANG MEMPENGARUHI KEPUASAN MAHASISWA STIE AMM DALAM PENGGUNAAN SISTEM INFORMASI SECARA ONLINE - Khotmi, Herawati; Amrul, Rusli; Astini, Yuli (Valid Jurnal Ilmiah, 2017)
One of the information technology developments by STIE AMM is the on-line academic system. This study aimed at identifying the effect of the students’ (user) interaction with information systems, Support/Reward/Punishment, information system security, information access speed/ease, information accuracy, computer network/Internet accessibility and utilities to the students’ satisfaction in using information system.Causality research was implemented in this study and it was conducted in STIE AMM Economics School. Questionnaires were employed to collect the data. 100 Students who are majoring accounting were chosen as the participant. The independent variables in this research were Support, Reward/Punishment, information systems security, information access speed/ease, information accuracy, computer network/internet accessibility and utilities. While dependent variable in this research was student satisfaction in using information system.Instrument analysis which is reliability and validity test was conducted and then continued with conducted the classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test before implementing the analysis phase. After conducting classical assumption test the next step was conducting multiple regression analysis using T-test, F-test and determination test.The results of hypothesis testing with T-test showed that Students’ (user) interaction with information systems, information systems security and accessibility and computer network/internet utility had a significant effect on student satisfaction in using the information system. While Support, Reward/Punishment, information access speed/ease and information accuracy had no effect to the students’ satisfaction in using information systems